Pengaruh Dukungan Organisasi, Dukungan Atasan, Dukungan Rekan Kerja yang Dirasakan, dan Konflik Pekerjaan-Keluarga terhadap Kinerja Karyawan dengan Burnout sebagai Variabel Intervening: Studi pada Karyawan Wanita PT. Arisamandiri Pratama - Annisa Nabila Ardya Wibowo; Mirwan Surya Perdhana (Faculty of Economics and Business Diponegoro University, 2025)
This study aims to examine the effect of perceived organizational support, supervisor support, co-worker support, and work-family conflict on employee performance with burnout as an intervening variable in female employees who face dual roles between work and family.This study uses the Non-Probability Sampling method by means of Purposive Sampling. While the sample used is 100 female full-time employees at PT Arisamandiri Pratama who have family responsibilities. The data analysis technique in this study uses Partial Least Squares Structural Equation Modeling (PLS-SEM) method using SmartPLS version 4.1.0.9 software to determine the path coefficient and the effect of the independent variables on the dependent variable.The results showed that perceived organizational support, supervisor support, and co-worker support had a negative and significant effect on burnout. Work-family conflict had a positive and significant effect on burnout. Burnout also had a negative and significant effect on employee performance. This study shows that burnout can mediate the effect of workplace support and work-family conflict on employee performance.